The Development of Whole Sporozoite Vaccines for Plasmodium falciparum Malaria - Itsara, Leslie S.; Zhou, Yaxian; Do, Julie; Grieser, Alexis M.; Vaughan, Ashley M.; Ghosh, Anil K. (Frontiers in Immunology, 2018)
Each year malaria kills hundreds of thousands of people and infects hundreds of millions of people despite current control measures. An effective malaria vaccine will likely be necessary to aid in malaria eradication. Vaccination using whole sporozoites provides an increased repertoire of immunogens compared to subunit vaccines across at least two life cycle stages of the parasite, the extracellular sporozoite and intracellular liver stage. Three potential whole sporozoite vaccine approaches are under development and include genetically attenuated parasites, radiation attenuated sporozoites, and wild-type sporozoites administered in combination with chemoprophylaxis. Pre-clinical and clinical studies have demonstrated whole sporozoite vaccine immunogenicity, including humoral and cellular immunity and a range of vaccine efficacy that depends on the pre-exposure of vaccinated individuals. While whole sporozoite vaccines can provide protection against malaria in some cases, more recent studies in malaria-endemic regions demonstrate the need for improvements. Moreover, challenges remain in manufacturing large quantities of sporozoites for vaccine commercialization. A promising solution to the whole sporozoite manufacturing challenge is in vitro culturing methodology, which has been described for several Plasmodium species, including the major disease-causing human malaria parasite, Plasmodium falciparum. Here, we review whole sporozoite vaccine immunogenicity and in vitro culturing platforms for sporozoite production.